Bio-inspired hierarchical nanoporous carbon derived from water spinach for high-performance supercapacitor electrode materials. Issue 5 (11th February 2022) - Lin, Xinyu; Xu, Yaping; Wu, Jinggao; Huang, Jing
Abstract : Due to various properties, green carbon nanomaterials with high specific surface area and environmentally friendly features have aroused extensive interest in energy storage device applications. Abstract : Due to various properties, green carbon nanomaterials with high specific surface area and environmentally friendly features have aroused extensive interest in energy storage device applications. Here, we report a facile, one-step carbonization of water spinach to synthesize porous carbon that exhibits a high specific surface area of ∼1559 m 2 g −1, high specific capacitance (∼1191 F g −1 at 1 A g −1 ), a low intercept (0.9 Ω), outstanding rate capability and superior cycling stability (94.3% capacitance retention after 10 000 cycles). Moreover, the assembled symmetric cell delivers a high energy density of ∼85 W h kg −1 at 1200 W kg −1 and ultra-high stability (loss of 6.8% after 10 000 cycles). An energy density of 49 W h kg −1 could also be achieved even with a power density of up to 24 kW kg −1, which indicates that this material could be a promising candidate for future applications in aqueous-based supercapacitors.